One Kind New Hybrid Power Mean and Its Computational Formulae - Li Wang; Xuexia Wang (Journal of Mathematics)
The main purpose of this study is to use the elementary and analytic methods and the properties of the classical Gauss sums to study the calculation problems of one kind of hybrid power mean involving the quadratic character sums and the two-term exponential sums and give an exact computational formula for it.